Whole-Genome Sequencing of a Salmonella enterica subsp. enterica Serovar Infantis Strain Isolated from Broiler Chicken in Peru - Vallejos-Sánchez, Katherine (Microbiol Resour Announc, 2019)
This report shows the whole-genome sequence of the multidrug-resistant Salmonella enterica subsp. enterica serovar Infantis strain FARPER-219. Antibiotic resistance genes are found mainly in the plasmid. Our findings show important genetic information that provides an understanding of the recent spread of this serotype in poultry.